2005
DOI: 10.1096/fj.05-4688fje
|View full text |Cite
|
Sign up to set email alerts
|

β‐Adrenergic receptor trafficking by exercise in rat adipocytes: roles of G‐protein‐coupled receptor kinase‐2, β‐arrestin‐2, and the ubiquitin‐proteasome pathway

Abstract: The effect of exercise on beta-adrenergic receptor (beta-AR) trafficking was investigated in rat adipocytes. The binding sites of a hydrophilic ligand, [(3)H]CGP12177, increased immediately (0 h) and at 3 h after exercise (3 h) but decreased at 24 h after exercise (24 h). The data of immunoblotting revealed that the alterations in the binding sites mainly paralleled the alterations in the beta2-AR proteins in membrane fractions. The protein expressions of both G-protein-coupled receptor kinase (GRK)-2 and beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 43 publications
1
15
0
Order By: Relevance
“…There is increasing evidence that obesity can be viewed as an inflammatory disorder, associated with increased circulating inflammatory cytokines and macrophage infiltration into fat, which in turn exacerbates defects associated with Type 2 Diabetes. PAR 2 has been implicated in numerous inflammatory pathways and there is some evidence that β-arrestin levels can be altered under different physiological conditions [37,38] and in a mouse model of insulin resistance (db/db mice)[39]. β-arrestins have also been reported to contribute to insulin resistance by mediating a TNFα-induced inflammatory pathway[40].…”
Section: Discussionmentioning
confidence: 99%
“…There is increasing evidence that obesity can be viewed as an inflammatory disorder, associated with increased circulating inflammatory cytokines and macrophage infiltration into fat, which in turn exacerbates defects associated with Type 2 Diabetes. PAR 2 has been implicated in numerous inflammatory pathways and there is some evidence that β-arrestin levels can be altered under different physiological conditions [37,38] and in a mouse model of insulin resistance (db/db mice)[39]. β-arrestins have also been reported to contribute to insulin resistance by mediating a TNFα-induced inflammatory pathway[40].…”
Section: Discussionmentioning
confidence: 99%
“…RNA extraction and RT-PCR analysis of mRNAs for ATGL and PPARg-2 and b-actin were performed using an RT-PCR system, as previously described [47], [48]. Twenty-five cycles of amplification were carried out for ATGL and PPARg-2 mRNAs, and 20 cycles were used for b-actin mRNA.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, there is little information on the response of β 2 -AR expression to exercise training in skeletal muscles. However, many studies demonstrate the effects of exercise training on β 2 -AR expression in several tissues and cell types such as myocardia [73, 74], adipocytes [75], and macrophages [76]. Barbier et al [73] demonstrated that exercise training induces changes in the distribution of β 1 -, β 2 -, and β 3 -AR densities in the rat left ventricle.…”
Section: Exercise Training and β2-armentioning
confidence: 99%
“…Barbier et al [73] demonstrated that exercise training induces changes in the distribution of β 1 -, β 2 -, and β 3 -AR densities in the rat left ventricle. In adipocytes, the exercise-induced trafficking of β 2 -AR into the cell membrane from the cytosol is coupled with adipocytes' function to increase intracellular cAMP production [75]. Kizaki et al [76] also found a reduction in the expression of β 2 -AR mRNA in macrophages and highlight the significance of β 2 -AR in the exercise training-induced improvement of macrophages' innate immune function.…”
Section: Exercise Training and β2-armentioning
confidence: 99%